(untitled) (Research, Society and Development, 2021)
It seems a cliché to talk about teacher training, more precisely about teacher education policies. For years, the degree course has been under different approaches, transmuting among different objectives, practices, curricula and professional profiles, according to current ideas that correspond to the transitory needs of governments. Currently, some advances have taken place in terms of rethinking degrees from the perspective of access and permanence, but there are still many gaps to be unraveled. Thus, from a bibliographical survey, this study aimed to discuss issues about teaching through a brief overview on its existence, some necessary differences between the degree and the baccalaureate, seeking to consolidate an identity as being endowed with the same rigors as other courses of graduation. And, finally, to point out some policies to strengthen demand, entry and permanence in the area of education in a purposefully superficial perspective in order to provoke debate in broader dimensions in the future. It could be verified then that, despite a very superficial genesis and the cooling of discourses of valuing teaching throughout history, teacher training has always gone through a fine line between emancipatory and mechanistic conceptions, but it continues to resist in the affirmation of its identity is marked by the indispensability of being at the center of debates at the micro and macro levels.